Synthesis of cytotoxic 2,2-difluoroderivatives of dihydrobetulinic acid and allobetulin and study of their impact on cancer cells - Borkova, Lucie; Jasikova, Lucie; Rehulka, Jiri; Frisonsova, Katerina; Urban, Milan; Frydrych, Ivo; Popa, Igor; Hajduch, Marian; Dickinson, Niall J; Vlk, Martin; Dzubak, Petr; Sarek, Jan (European journal of medicinal chemistry, 2015)
In this article, we describe the preparation and cytotoxic properties of a small focused library of lupane and 18α-oleanane triterpenoids that contain a combination of two structural motifs known to enhance the biological activities. First, we introduced two fluorine atoms to position 2 of the skeleton. Second, we synthesized a set of hemiester prodrugs, which were intended to increase the solubility and activity. Starting from betulin, we obtained two hydroxyketones (derivatives of dihydrobetulinic acid and allobetulin) and their fluorination using DAST provided 2,2-difluoro-3-oxo-compounds as the main products. Then the 3-oxo group in each derivative was reduced by NaBH4 to obtain 3β-hydroxy compounds suitable for modifying by various hemiesters. We prepared 21 compounds, 11 of them new, their cytotoxicity was tested on T lymphoblastic leukemia CCRF-CEM cells first and the most active derivatives were selected for screening on another six tumor and two non-tumor cell lines. All of them showed selectivity against cancer lines with therapeutic index between 2 and 8. All hemiesters had activity in the same range as the free hydroxyl derivatives and they would be suitable prodrugs for future in vivo experiments. Interestingly, all hemiesters of 2,2-difluorodihydrobetulonic acid had higher activity against p53 knock-out p53-/- cancer cell line than against the non-mutated analog. In active derivatives, the cell cycle was analyzed by flow cytometry and several compounds slowed down cell cycle progression through G0/G1 or S-phase.
Keywords: molekulární konformace; Molecular Conformation; Synthesis; Cytotoxic; Drug Screening Assays, Antitumor; Antineoplastic Agents, Phytogenic; Humans; Tumor Cells, Cultured; fytogenní protinádorové látky; Cell Cycle; vztahy mezi strukturou a aktivitou; Structure-Activity Relationship; Dose-Response Relationship, Drug; Triterpenes; Betulinic acid; lidé; proliferace buněk; Testing; apoptóza; nádorové buňky kultivované; triterpeny; Cell Proliferation; Fluoroderivatives; Hydrocarbons, Fluorinated; screeningové testy protinádorových léčiv; vztah mezi dávkou a účinkem léčiva; fibroblasty; fluorované uhlovodíky; buněčný cyklus; Apoptosis; Fibroblasts